THE RELATIONSHIP TYPE OF PERSONALITY WITH HYPERTENSION DEGREES ON HYPERTENSION PATIENS OF WOMEN 30 – 50 YEARS IN PUSKESMAS PAJANG SURAKARTA - Anis Prabowo; Azizah Rohmah (MOTORIK Jurnal Ilmu Kesehatan, 2018)
Background:Hypertension is a cardiovascular disease commonly called the silentkiller because hypertension is a hidden killer. Several factors that affect theoccurrence of hypertension are factors that can be changed and can not bechanged. In addition, hypertension can also be caused by tension, anxiety, socialstatus and personality type. Purpose: This study aims to determine the relationshipof personality type to the incidence of hypertension. The type of this research isdescriptive correlation with cross sectional design. Research Methods:Thisresearch was conducted at Puskesmas Pajang Surakarta on October 2017-March2018. The type of this research is descriptive correlation with cross sectionaldesign. Samples were 30 respondents of hypertension patients). Samplingtechnique using accidental sampling. The data were collected by usingquestionnaires. Data analysis used univariate and bivariate analysis using chisquaretest. Results: this research took 30-50 years old female respondents that is30 respondents with hypertension of degree1 as much as 9 people 30.0%, degree2as many as 5 people 16.7%, degree3 16 people 53.3% and there are 22 people73.3% with personality type A and 8 people 26.7% personality type B. Bivariateanalysis shows that there is a relationship of personality type with the incidenceof hypertension with value (p = 0.000, 0.000). Conclusion: There is a relationshipbetween personality type A and B with degree of hypertension where personalitytype A is more likely to have hypertension than personality type B.